2012
DOI: 10.1038/sc.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity changes in SCI following a dynamic standing program using the Segway

Abstract: Study design: A pilot prospective pre-and post-intervention study. Objectives: To determine whether a dynamic standing program using the Segway Personal Transporter results in any measurable physiological effects in individuals with spinal cord injury (SCI) using both qualitative and quantitative measures of spasticity, pain and fatigue. Setting: International Collaboration of Repair Discoveries (ICORD) Research Centre, Vancouver, BC, Canada. Methods: Eight individuals with SCI ASIA (American Spinal Injury Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…50, 51, 52, 53 Apparent spastic behavior was not detected in our model, which may be due to the lack of an appropriate parameter for assessing spastic behavior in rodents. Given that we did not clearly observe spastic behavior, we are currently trying to detect abnormal muscle contractions or neuromuscular junction changes using morphological analyses.…”
Section: Discussionmentioning
confidence: 72%
“…50, 51, 52, 53 Apparent spastic behavior was not detected in our model, which may be due to the lack of an appropriate parameter for assessing spastic behavior in rodents. Given that we did not clearly observe spastic behavior, we are currently trying to detect abnormal muscle contractions or neuromuscular junction changes using morphological analyses.…”
Section: Discussionmentioning
confidence: 72%
“…However, beliefs about the therapeutic effects of standing on spasticity are primarily based on the results of surveys, case series and case reports. [4][5][6]8,[12][13][14] There are as yet no high-quality trials that have provided convincing evidence that standing decreases spasticity. We therefore included spasticity as a secondary outcome to further explore this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest to this trial is not only the claim that regular standing improves bowel function but also that it reduces spasticity. [4][5][6]8,[12][13][14] It is believed that the stretch associated with standing dampens the reflex arc. There is some interim evidence to support this belief particularly from studies showing an immediate decrease in spasticity with one-off stretches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with different functional levels and varying degrees of strength, range of motion and balance found that they could easily and safely drive the Segway. 10 In a small pilot study of eight individual with SCI, Boutilier et al 11 showed that spasticity decreased significantly immediately after using a Segway as measured by the Modified Ashworth Scale (MAS); however, no long-term benefits were observed over a month of use.…”
Section: Introductionmentioning
confidence: 99%